Airbnb customer experience: Evidence of convergence across three countries. (March 2017) - Brochado, Ana; Troilo, Michael; Shah, Aditya
Highlights: We test convergence regarding customer experiences in the hospitality realm. We examine 1, 776 Airbnb web reviews across the US, Portugal, and India. Using thematic analysis, we find support for convergence of consumer experiences. Our contribution is this analysis and finding of consumer convergence.